Gout. Issue 10287 (15th May 2021) - Dalbeth, Nicola; Gosling, Anna L; Gaffo, Angelo; Abhishek, Abhishek
Summary: Gout is a common and treatable disease caused by the deposition of monosodium urate crystals in articular and non-articular structures. Increased concentration of serum urate (hyperuricaemia) is the most important risk factor for the development of gout. Serum urate is regulated by urate transporters in the kidney and gut, particularly GLUT9 (SLC2A9), URAT1 (SLC22A12), and ABCG2. Activation of the NLRP3 inflammasome by monosodium urate crystals with release of IL-1β plays a major role in the initiation of the gout flare; aggregated neutrophil extracellular traps are important in the resolution phase. Although presenting as an intermittent flaring condition, gout is a chronic disease. Long-term urate lowering therapy (eg, allopurinol) leads to the dissolution of monosodium urate crystals, ultimately resulting in the prevention of gout flares and tophi and in improved quality of life. Strategies such as nurse-led care are effective in delivering high-quality gout care and lead to major improvements in patient outcomes.